Fly high, Lolo - Daly, Niki; Daly, Niki (2022)
"More fun is on the way for Lolo in Fly High, Lolo, the fourth book in Niki Daly's Lolo series for beginning readers. Lolo is kind-hearted, creative, full of joy, and- whether it's making homemade Christmas decorations from recycled plastics, or stepping in when the school play goes awry-she always knows just what to do to save the day! In this collection of easy-to-read stories, we meet Lolo, a girl who lives in South Africa with her mother and grandmother, Gogo. Charmingly illustrated by the author, Fly High, Lolo follows Lolo as she explores her world, and the new adventures each day brings. In Fly High, Lolo, Lolo gets an unexpected role in the school play, meets Miss Teen the Beauty Queen, goes on a beach clean-up with Mama's new friend, and makes beautiful recycled Christmas decorations"--
Ages 5-7
Grades K-1